Écriture Feminine and the Poetry of Langston Hughes - Das, Shruti (Literary Studies, 2021)
This paper attempts to locate Hughes’s poetic diction as Ecriture feminine since like feminist poetry the diction of his poetry is rebellious and questions the hierarchical structure of society where White people hold more power and promote the idea of racial superiority. His desire to express the angst of the Blacks finds currency in the definition and explication of feminine writing. The focus of this paper will be on analysis of the poetry of Langston Hughes in the light of ecriture feminine in order to show how Hughes counters hegemony’s repressive rhetoric, challenges the loss of agency through the language of the dominant class and recreates another symbolic order.